Solidarity Economy Alternative Spaces, Power and Politics - Esteves, A.; Hefrey, T.; Lucas dos Santos, L; Leal, L. (2023)
Solidarity economy-based alternative spaces result from an interface among structural factors, institutional regimes and forms of collective action that mobilise narratives of change, collective identities and non-capitalist economic practices. This book analyses how solidarity economy initiatives develop alternative spatialities as counterpower to mainstream economy. Based on case studies in Europe, Latin America, Africa and Asia, it elaborates on how different scales of solidarity economy-based alternative spaces result from an interface among structural factors, institutional regimes and forms of collective action that mobilise narratives of change, collective identities and non-capitalist economic practices.